2014
DOI: 10.1016/j.jped.2014.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of therapeutic approach on the neonatal evolution of very low birth weight infants with patent ductus arteriosus

Abstract: The conservative approach of PDA was associated to high mortality, the surgical approach to the occurrence of BPD36wks and ROPsur, and the pharmacological treatment was protective for the outcome death/BPD36wks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…Studies in baboons support the perspective that surgical ligation may in fact produce detrimental effects on lung development in preterm infants ( 34 ). Infants treated with prostaglandin inhibitors for PDA have lower rates of BPD and mortality than those treated with surgical ligation ( 35 ). It is speculated that the different effects of pharmacological and surgical closure of PDA on the development of BPD may be related to the anti-inflammatory effects of the medications (ibuprofen or indomethacin) used to close the ductus ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in baboons support the perspective that surgical ligation may in fact produce detrimental effects on lung development in preterm infants ( 34 ). Infants treated with prostaglandin inhibitors for PDA have lower rates of BPD and mortality than those treated with surgical ligation ( 35 ). It is speculated that the different effects of pharmacological and surgical closure of PDA on the development of BPD may be related to the anti-inflammatory effects of the medications (ibuprofen or indomethacin) used to close the ductus ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that persistent PDA was significantly associated with increased duration of mechanical ventilation, oxygen treatment and rates of BPD ( 25 ). Sadeck et al ( 26 ) reported that the conservative approach to PDA was associated with high mortality, the surgical approach to the occurrence of BPD at 36 weeks, and pharmacological treatment was protective for the outcome of mortality or BPD at 36 weeks. The present study had similar observations.…”
Section: Discussionmentioning
confidence: 99%
“…[6,11,43,45,47,63]. In the short term, PDA is associated with arterial hypotension, myocardial dysfunction and systemic perfusion [5,8,38], renal functional disturbances [5,19,39], and pulmonary hemorrhage [40,64,65].…”
Section: Respiratory Distress Syndrome and Patent Ductus Arteriosus Imentioning
confidence: 99%
“…In the short term, PDA is associated with decreased blood pressure [5,8], decreased renal function [5], cardiac congestive failure [18,37,38], pulmonary haemorrhage [8,39], apnea and ventilator-dependency [6,38], bronchopulmonary dysplasia (BPD) [5,14,20,21,25,34,41,42], necrotizing enterocolitis (NEC) [8,9,11,19,20,34,39,43,44], intraventricular hemorrhage (IVH) [5,19,20,39,42,45,46], periventricular leukomalacia (PVL) [5], retinopathy of prematurity (ROP), cerebral palsy [24], delayed growth [11], and increased mortality rate [6,34,45,[47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%